"The heart of the village" : what determined the spatial distribution of North Canterbury rural schools 1850-1940? - Davies, Angela Mary Frances (University of Canterbury. Department of Geography, 2009)
When the Province of Canterbury was established by the Canterbury Association its founders looked at the English system of education and saw many of its problems. Education was seen as a panacea for many of the ills of the 19th century but the system in Britain was dependent on the churches, and with the increasing population and rural-urban migration the system became overloaded. A factor which saw state involvement become essential. As the Canterbury founders wanted to avoid importing many of the British problems education was seen as a high priority. This thesis looks at how the state influenced the development of the education system in the North Canterbury Education Board region, as defined in 1900, over the period of 1850 to 1940. With the spatial distribution of elementary schools and their effects on the community being of particular interest. In Canterbury while the initial momentum originated from the aims of the founders, the rural communities took the initiative and following meetings, and some Education Board funding, they founded area schools. Attention is paid to the school as the "heart of the village" and its use for many non-educational purposes. These included utilisation as the post-office, the library, the museum and the entertainment, social and sporting centre. A special look is taken at the transport advancements which led to the loss of services in many rural areas and thus the loss of population and a decline in school rolls. This in turn led to the beginning of the school bus service in 1924 and the acceleration of the closure of many small schools as a system of consolidations took place. Many of the changes in the spatial distribution of schools in the North Canterbury region were due to the actions of the state in the passing of various regulations the first and most pivotal during the period studied, 1850-1940, being that of the 1877 Education Act. This was followed by many others, the most important dealing compulsory attendance, another factor influential in changing the map of schools in the region. From this study it can be seen that the school was regarded as being the most important feature of the community. Regardless of age or religious beliefs everyone was able to have an interest in it and the school acted as a unifying factor for the district.